2018
DOI: 10.15448/1980-6523.2017.3.26352
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of odontogenic pain and associated factors in children treated at a pediatric dental emergency service

Abstract: OBJECTIVE: To describe the prevalence and to analyze the factors associated with odontogenic pain among children at a pediatric dental emergency service. METHODS: The retrospective cross-sectional study was performed using the clinical records of children (0 to 12 years old) attended from 2003 to 2010 at the Pediatric Dentistry Emergency Service of the Universidade Federal do Espírito Santo. The information was collected by a researcher, and a structured form was used to collect all data from patients' records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Evidentemente, essa exposição dos acadêmicos para executar todos os procedimentos é necessária para desenvolver habilidades clínicas e competências essenciais, com o intuito de aumentar a confiança para atender crianças como profissionais generalistas (Rodd et al, 2010;Spiritoso et al, 2015;Sonbol, Abu-Ghazaleh, & Al-Bitar, 2017), considerando que estes não devem necessariamente conhecer os pormenores de cada especialidade, mas ter uma visão geral para oferecer resolubilidade na maioria dos casos (Lage, Almeida, Vasconcelos, Assaf, & Robles, 2017). Em contrapartida, tem sido discutido que a formação do cirurgião-dentista pode estar inadequada na prática clínica devido à redução do número de crianças na triagem das faculdades e à menor quantidade das necessidades de tratamento (Vyawahare et al, 2013;Casamassimo & Seale, 2015), fato este que não se constatou como contratempo no presente estudo, devido à grande procura por atendimento de urgência odontopediátrica nessa mesma clínica (Muller et al, 2017).…”
Section: Discussionunclassified
“…Evidentemente, essa exposição dos acadêmicos para executar todos os procedimentos é necessária para desenvolver habilidades clínicas e competências essenciais, com o intuito de aumentar a confiança para atender crianças como profissionais generalistas (Rodd et al, 2010;Spiritoso et al, 2015;Sonbol, Abu-Ghazaleh, & Al-Bitar, 2017), considerando que estes não devem necessariamente conhecer os pormenores de cada especialidade, mas ter uma visão geral para oferecer resolubilidade na maioria dos casos (Lage, Almeida, Vasconcelos, Assaf, & Robles, 2017). Em contrapartida, tem sido discutido que a formação do cirurgião-dentista pode estar inadequada na prática clínica devido à redução do número de crianças na triagem das faculdades e à menor quantidade das necessidades de tratamento (Vyawahare et al, 2013;Casamassimo & Seale, 2015), fato este que não se constatou como contratempo no presente estudo, devido à grande procura por atendimento de urgência odontopediátrica nessa mesma clínica (Muller et al, 2017).…”
Section: Discussionunclassified
“…Children can also refuse consent, which means they do not agree to participate. The age at which consent is requested varies and can be as young as 7 years old [ 2 ]. Consent is not required by law, but in our study we required children who were developmentally and cognitively able to participate in decision making.…”
Section: Methodsmentioning
confidence: 99%
“…Although local anesthesia (LA) is used as an important tool for reducing pain and anxiety, paradoxically, pain during needle insertion and loss of normal sensations secondary to anesthesia frequently causes non-compliance in children. It has been demonstrated that its effect lasts longer than the maximum time required for the most common dental procedures to be completed [ 2 ]. However, this prolonged soft-tissue anesthesia is inconvenient, unnecessary, or detrimental, especially in children, and a higher risk of self-injury has been reported, but there have been few studies on acceleration of recovery to normal sensation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in pain experience are explained, among other things, by differences in pain threshold and tolerance. In addition, it is related to sensitivity (extension and localization of tissue lesion), genetic (related to the nociceptive system and pain modulation) cultural (learning, experience, symbolic meaning of pain (4). Oral diseases can cause pain, suffering, and mental distress that can cause harm to people (5).…”
Section: Introductionmentioning
confidence: 99%